TEKNOLOGI INFORMASI DAN PENDIDIKAN ISLAM - Ah. Subhan (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
The Era of globalization has resulted in the rapid and rapid development of science and technology, especially with information technology. The result is an explosion of information that is a sign of the opportunities and challenges that people will face in the future. However, we need to be aware even though the technological advances are beneficial, but not many of the negative impacts it can bring. It is necessary for an educational pattern to be proportionally integrated. Islamic education with the foundation of the Qur'an and Hadith, in principle, has given high enough motivation so that people are advanced and able to be the caliphate on the earth, in order to achieve true prosperity. Thus, education should be fully responsive to the changes and demands of the times, especially in relation to the development of information-communication technology, as well as being a technology-based Islamic education amplifier, particularly Communication technology to be able to truly have great benefits for the world society. Keyword: Islamic Education, information technology, globalization